(untitled) (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2025)
This study focuses on the effect of speech acts on EFL students’ speaking skills in Indonesia against the background of students’ low speaking skills in EFL classrooms due to the lack of use of structured communication strategies. This study aims to analyse the impact of systematic use of speech acts on students’ speaking skills in an EFL learning environment. Using a qualitative approach with a case study design, this research involved 20 students from the English Education Department of the State Islamic University of North Sumatra as participants. Data were collected through observations and interviews that took place during three learning sessions including pre-test, test and post-test. Qualitative descriptive analysis showed that the number and complexity of students’ speech acts increased significantly, while their confidence and active participation in speaking English also increased. In conclusion, speech acts can be an effective strategy for improving EFL students’ speaking skills, with the implication that this approach deserves wider application in English language learning in Indonesia.